β-cell Regenerative Potential of Selected Herbal Extracts in Alloxan Induced Diabetic Rats - Attanayake, Anoja P.; Jayatilaka, Kamani Ayoma Perera Wijewardana; Mudduwa, Lakmini K. B.; Pathirana, Chitra (Current Drug Discovery Technologies, 2019)
Background: Effective β-cell regeneration is a recognized therapeutic strategy in the treatment of type 1 diabetes mellitus. Regeneration of β-cells could be achieved via exogenous natural sources as medicinal plant extracts. Medicinal plants selected for the investigation were Spondias pinnata (Linn. f.) Kurz, Coccinia grandis (L.) Voigt and Gmelina arborea Roxb. The objective was to determine the β-cell regenerative potential of these plant extracts in alloxan-induced diabetic rats. Alloxan monohydrate was used to induce diabetes (150 mg/kg, ip). Methods: Wistar albino rats were divided into six groups (n=6); healthy untreated rats (healthy control), alloxan-induced diabetic untreated rats (diabetic control), diabetic rats received the extracts (treatment groups) of S. pinnata (1.0 g/kg), C. grandis (0.75 g/kg), G. arobrea (1.00 g/kg) and diabetic rats received glibenclamide (0.5 mg/kg; positive control). The above treatment was continued for 30 days. On the 30th day, the rats were sacrificed and biochemical parameters were determined. In addition, histopathology and immunohistochemistry on the pancreatic tissue were done on the 30th day. Results: According to the results obtained for biochemical parameters, there was a significant increase in the concentrations of serum insulin and C-peptide in plant extracts treated diabetic rats (p < 0.05). The extract of C. grandis produced the highest degree of β-cell regeneration demonstrated through an increase in the number of islets and percentage of the insulin-secreting β-cells (75%) in the pancreas of diabetic rats (p < 0.05) based on the histopathology and immunohistochemistry findings. Conclusion: The results revealed that the selected extracts of C. grandis (0.75 g/kg), G. arborea (1.00 g/kg) and S. pinnata (1.00 g/kg) exerted β-cell regenerative potential in diabetic rats. The three plant extracts would be valued as natural agents of prompting the β-cell regeneration in vivo.
Keywords: Gmelina arborea